A multicenter phase II study of sunitinib in patients with locally advanced or metastatic differentiated, anaplastic or medullary thyroid carcinomas: mature data from the THYSU study. (May 2017) - Ravaud, Alain; de la Fouchardière, Christelle; Caron, Philippe; Doussau, Adelaïde; Do Cao, Christine; Asselineau, Julien; Rodien, Patrice; Pouessel, Damien; Nicolli-Sire, Patricia; Klein, Marc; Bournaud-Salinas, Claire; Wemeau, Jean-Louis; et al.
Abstract: Purpose: Patients with advanced radioactive iodine resistant differentiated (MDTC) or medullary (MMTC) thyroid cancer had an unmet need. Early data showed promising efficacy of vascular endothelial growth factor receptor inhibitors. We investigated sunitinib in this setting. Patients and methods: This phase 2 trial enrolled MDTC, anaplastic (MATC) and MMTC patients in 1st line anti-angiogenic therapy with sunitinib at 50 mg/d, 4/6w. Objective response rate was the primary end-point. Secondary end-points were progression-free survival, overall survival and safety. Results: Seventy-one patients were enrolled from August 2007 to October 2009, 41 MDTC/4 MATC patients and 26 MMTC patients. Patients received a median of 8 and 9 cycles, respectively. In the MDTC/MATC group, 13% of patients and 43% of cycles and in the MMTC group, 23% of the patients and 48.8% of cycles remained at 50 mg/d, respectively. The primary end-point was reached with an objective response rate of 22% (95% CI: 10.6–37.6) in MDTC patients and in 38.5% (95% CI: 22.6–56.4) in MMTC patients. No objective response was seen in MATC patients. Median progression-free survival and overall survival were 13.1 and 26.4 months in MDTC patients, 16.5 and 29.4 months in MMTC patients. The most frequent side effects were asthenia/fatigue (27.8% ≥ grade 3), mucosal (9.9% ≥ grade 3), cutaneous toxicities, hand-foot syndrome (18.3% ≥ grade 3). Of all, 14.1% had a cardiac event. Nine unexpected side effects were reported, out of which, five induced deaths. Conclusion: Sunitinib is active in MDTC and MMTC patients. Side effects were more severe than with previous reports. If using sunitinib, alternative schedule/dosage should be considered. Highlights: Sunitinib, a VEGFR/PDGFR TKI, has activity in metastatic thyroid carcinoma. Objective response rate is reported in metastatic differentiated and medullary thyroid carcinoma. Adverse events were more pronounced with sunitinib: 50 mg/d, 4/6w suggesting to use other schedule or dosage of sunitinib.